DEIXIS IN JULIAN TREASURE’S TEDTALKS : “HOW TO SPEAK SO THAT PEOPLE WANT TO LISTEN” - Sihombing, Meyta Isenda P.; Silalahi, Charles David Marudut (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
This research analyzes Julian Treasure's use of deixis in his TED Talk, "How to Speak So That People Want to Listen. The study identifies and classifies the differences of deictic expressions used in the conversation by using a pragmatic analysis approach. The results show that Treasure makes good use of person, spatial, temporal, discourse, and social deixis to improve clarity in speech and engagement among audiences. This analysis advances our knowledge of deixis's role in spoken discourse and its importance for persuasive public speaking.